Impairment of CD4+ cytotoxic T cells predicts poor survival and high recurrence rates in patients with hepatocellular carcinoma12. Issue 1 (15th February 2013) - Fu, Junliang; Zhang, Zheng; Zhou, Lin; Qi, Zhaorui; Xing, Shaojun; Lv, Jiyun; Shi, Jianfei; Fu, Baoyun; Liu, Zhenwen; Zhang, Ji‐Yuan; Jin, Lei; Zhao, Yulai; et al.
Abstract The role of CD4+ cytotoxic T cells (CTLs) in hepatocellular carcinoma (HCC) remains obscure. This study characterized CD4+ CTLs in HCC patients and further elucidated the associations between CD4+ CTLs and HCC disease progression. In all, 547 HCC patients, 44 chronic hepatitis B (CHB) patients, 86 liver cirrhosis (LC) patients, and 88 healthy individuals were enrolled in the study. CD4+ CTLs were defined by flow cytometry, immunohistochemistry, and lytic granule exocytosis assays. A multivariate analysis of prognostic factors for overall survival was performed using the Cox proportional hazards model. Circulating and liver‐infiltrating CD4+ CTLs were found to be significantly increased in HCC patients during early stage disease, but decreased in progressive stages of HCC. This loss of CD4+ CTLs was significantly correlated with high mortality rates and reduced survival time of HCC patients. In addition, the proliferation, degranulation, and production of granzyme A, granzyme B, and perforin of CD4+ CTLs were inhibited by the increased forkhead/winged helix transcription factor (FoxP3+) regulatory T cells in these HCC patients. Further analysis showed that both circulating and tumor‐infiltrating CD4+ CTLs were independent predictors of disease‐free survival and overall survival after the resection of the HCC. Conclusion: The progressive deficit in CD4+ CTLs induced by increased FoxP3+ regulatory T cells was correlated with poor survival and high recurrence rates in HCC patients. These data suggest that CD4+ CTLs may represent both a potential prognostic marker and a therapeutic target for the treatment of HCC. (HEPATOLOGY 2013)